Peran Pendidikan Kewarganegaraan dalam Membentuk Etika Digital Peserta Didik di Era Globalisasi Teknologi dan Media Sosial - Rahayu, Yayuk Muji; Rahman, Arip; Nurjanah, Eka; Ningsih, Indah Fuji; Mardiana (Academy of Social Science and Global Citizenship Journal, 2025)
Civics education plays a strategic role in developing digitally ethical students. Through this education, students are taught moral, ethical, and national values ​​in the era of technological globalization. These values ​​are crucial for developing a peaceful, ethical, and moral young generation. Civic education fosters national identity and tolerance for diversity among students. This study aims to determine the role of civic education in shaping students' digital ethics in the era of technological globalization and social media. This research method uses literature analysis and relevant expert theory to explore the dynamics of digital ethics behavior among students. This research identified elements such as digital ethics, the role of civics education, and other issues faced in the digital world. This study found that civics education plays a crucial role in shaping students' digital ethics in the era of technological globalization and social media. By explaining various factors that influence digital ethics, such as social media platform design, freedom of expression, and protection against hate speech, this study provides in-depth insights into the impact of civic education on the formation of students' digital ethics. In facing the complex dynamics of the digital space in the era of technological globalization, the role of civic education in integrating students' digital ethics into the curriculum is key to forming a young generation that is skilled in technology, digitally ethical, and responsible in online behavior. Using this approach, civics education can shape ethically aware, responsible, and students, creating a digital generation that positively impacts society as a whole.